Implementasi Media Visual Dan Implikasinya Terhadap Kemampuan Membaca Huruf Hijaiyah Peserta Didik Di SDN 5 Tomilto Kabupaten Gorontalo Utara - Lasindrang, Moh Tri Loisen; Yasin, Zohra; Abdullah Buhungo, Ruwiah (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This study aims to investigate the implementation of visual media and its implications for students’ ability to read Hijaiyah letters at SDN 5 Tomilito, North Gorontalo Regency. The research background is based on the difficulties students face in recognizing the unique forms of Hijaiyah letters, which differ significantly from Latin letters. The research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The findings indicate that the use of visual media, such as images, PPT projector displays, animated cartoons, and student textbooks, positively impacts students. They find it easier to recognize letters, distinguish between them, and read them correctly. The results show that visual media enhances students’ reading ability and learning motivation. It also facilitates understanding and recognition of Hijaiyah letters, particularly in pronunciation and letter forms. Consequently, students’ ability to read Hijaiyah letters improved significantly, as evidenced by increased reading accuracy and speed. Therefore, the researcher recommends the development of more varied visual media and teacher training to maximize the use of media in learning.